Increasing prevalence of primary biliary cholangitis in Victoria, Australia. Issue 4 (28th December 2019) - French, Janine; van der Mei, Ingrid; Simpson, Steve; Ng, Justin; Angus, Peter; Lubel, John; Nicoll, Amanda; Sood, Siddharth; Roberts, Stuart K; Kemp, William; Arachchi, Niranjan; Dev, Anouk; et al.
Abstract: Background and Aim: The prevalence of primary biliary cholangitis (PBC) reported in different countries varies significantly and in some parts of the world appears to be increasing. The aim of this study was to determine the 2013 prevalence of PBC in Victoria, Australia, and to determine the time trend by comparing it with previous studies undertaken in 1991 and 2002. Methods: Four case‐finding methods were used to identify cases of PBC in Victoria: (1) physicians' survey; (2) tertiary hospital search; (3) liver transplant database search; and (4) private pathology antimitochondrial antibody search. Results: The prevalence of PBC in Victoria, Australia, is 189.0 per million using all four methods. The average annual increase in prevalence from 1991 to 2013 was 7.7 per million per year. Using the same case‐finding methods as the 1991 Victorian prevalence study (methods 1 and 2), the prevalence of PBC increased from 19.1 per million in 1991 to 49.4 per million in 2002 ( P  < 0.001) and to 80.7 per million in 2013 ( P  < 0.001). Conclusions: The current prevalence of PBC in Victoria is significantly higher than previously reported. The use of private pathology‐based case‐finding methods is important in identifying the maximum number of PBC cases.